Framework for adopting sustainability in the supply chain. (2015) - Tiwari, Saurabh
Supply chain sustainability is progressively acknowledged as a significant component of corporate concern. It is the management of environmental, social and economic impacts, and the reinforcement of good governance practices, throughout the lifecycles of goods and services. It is viewed as the improved management of supply chain through the combination of social, environmental and economic issues making it a vital criterion in business decision making. The main driver for this changeover have been the rapid growth in industrialisation over the last few decades and in-turn lead to an increase in production and consumption of various goods and has done substantial amount of damage to the society and environment including depletion of natural resources and wastes generation during production. Thus, the purpose of this paper is to review the literature on sustainable supply chain which helps in developing a comprehensive understanding of sustainable supply chain management and provides a framework for sustainable supply chain, which can help organisation to achieve indispensable returns.